Fire in Orbit: Equipping the Commercial Spaceflight Industry for Fighting Fire in Micro-Gravity - Cybela, Trent (Proceedings of the Wisconsin Space Conference, 2015)
For several years, Orbital Technologies (ORBITEC) has had keen interest in the development of a portable fire suppression system intended for use in commercial spaceflight applications. With the aid of recent developments in fine water mist (FWM) atomization technologies, and partnerships with the University of Wisconsin – Platteville, work is commencing to develop a portable fire extinguisher (PFE). The extinguisher will be capable of operation in both gravity and microgravity environments regardless of orientation, and eliminate the use of toxic carbon dioxide as a fluid suppressant. The extinguisher will take advantage of the unique physics of microgravity to better suppress fires compared to previously used equipment. The following report outlines baseline research into the historical precedence of spacecraft fires, and common modes of fire ignition in microgravity. From this information we investigate design considerations necessary for the construction of a prototype PFE, as well as the market value of such a device.